2017
DOI: 10.1111/sdi.12616
|View full text |Cite
|
Sign up to set email alerts
|

Role of vascular calcification inhibitors in preventing vascular dysfunction and mortality in hemodialysis patients

Abstract: Cardiovascular events make up the primary cause of death in hemodialysis patients, and the risk for cardiovascular mortality is significantly increased by vascular calcification, a condition observed frequently in this patient population. The mechanisms underlying the pathogenesis of vascular calcification are complex, and many factors facilitate or hinder the development of calcification. In this review, we first summarize the main factors contributing to the pathogenesis of vascular calcification in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 105 publications
1
17
0
Order By: Relevance
“…While many studies have demonstrated the cell toxicity of CaP crystals, it became very clear that highly complex mechanisms exist to control the formation, maturation and pathogenicity of these mineral nucleation sites. This is in line with the currently accepted notion that VC is an active, naturally occurring, and tightly regulated multifactorial process, that must be actively inhibited (extensively reviewed elsewhere [16,86,87]). In fact, CaP nanocrystals are constituents of calciprotein particles (CPPs), mineralization-competent extracellular vesicles (EVs), and mineralized material deposited in the ECM of blood vessels.…”
Section: Role Of Phosphate Calcium and Calcium-phosphate Mineral In supporting
confidence: 85%
“…While many studies have demonstrated the cell toxicity of CaP crystals, it became very clear that highly complex mechanisms exist to control the formation, maturation and pathogenicity of these mineral nucleation sites. This is in line with the currently accepted notion that VC is an active, naturally occurring, and tightly regulated multifactorial process, that must be actively inhibited (extensively reviewed elsewhere [16,86,87]). In fact, CaP nanocrystals are constituents of calciprotein particles (CPPs), mineralization-competent extracellular vesicles (EVs), and mineralized material deposited in the ECM of blood vessels.…”
Section: Role Of Phosphate Calcium and Calcium-phosphate Mineral In supporting
confidence: 85%
“…These effects can be exacerbated by insufficient activity of calcification inhibitors, including magnesium, vitamin K, or reduced klotho expression. 67,68 For instance, phosphorus loading and klotho depletion consistently induce calcification and reduce vascular compliance in vitro and in vivo in animals. 6971 Similarly, restoration of normal klotho expression in animals with vitamin D agonists, or reduction in phosphorus exposure through diet can reverse or prevent the calcific phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…2 4 Vascular calcification is particularly prevalent and severe in patients with type 2 diabetes mellitus 3,5 and in those with advanced chronic kidney disease. 6,7 Sclerostin is expressed in calcifying vasculature during the highly regulated process of vascular smooth muscle cell (VSMC) reprogramming and differentiation to mineralizing osteoblast-like cells. 2 4,7 Thus, Scl may be regarded as part of a local counterregulatory mechanism to suppress vascular calcification.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Sclerostin is expressed in calcifying vasculature during the highly regulated process of vascular smooth muscle cell (VSMC) reprogramming and differentiation to mineralizing osteoblast-like cells. 2 4,7 Thus, Scl may be regarded as part of a local counterregulatory mechanism to suppress vascular calcification. 2,6 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation